2022
DOI: 10.1186/s12893-022-01621-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy during the COVID-19 pandemic in a tertiary care hospital in Germany: higher rates of acute and gangrenous cholecystitis in elderly patients

Abstract: Background The COVID-19 pandemic caused a global health crisis in 2020. This pandemic also had a negative impact on standard procedures in general surgery. Surgeons were challenged to find the best treatment plans for patients with acute cholecystitis. The aim of this study is to investigate the impact of the COVID-19 pandemic on the outcomes of laparoscopic cholecystectomies performed in a tertiary care hospital in Germany. Patients and methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
(24 reference statements)
0
7
0
3
Order By: Relevance
“…Rahimi et al. [ 13 ] konnten an 182 Patienten präsentieren, dass die histologische Untersuchung von Gallenblasen bei älteren Patienten während der COVID-19-Pandemie mehr akute und gangränöse Befunde aufwiesen. Dass der Schweregrad der Erkrankung im Rahmen der COVID-19-Pandemie angestiegen ist, wird von Koch et al.…”
Section: Hintergrundunclassified
See 2 more Smart Citations
“…Rahimi et al. [ 13 ] konnten an 182 Patienten präsentieren, dass die histologische Untersuchung von Gallenblasen bei älteren Patienten während der COVID-19-Pandemie mehr akute und gangränöse Befunde aufwiesen. Dass der Schweregrad der Erkrankung im Rahmen der COVID-19-Pandemie angestiegen ist, wird von Koch et al.…”
Section: Hintergrundunclassified
“…Im Gegenteil, die postoperative Komplikationsrate fiel in der Gruppe Cov19 eher ab (Daten nicht gezeigt). Die Beobachtung, dass auch ältere Patienten während der COVID-19-Pandemie öfter mit schweren Verläufen zur Operation kamen, wurde in anderen Untersuchungen bestätigt [ 6 , 13 ].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Although cholecystectomy is recommended after endoscopic papillotomy for common bile duct stones concomitant with gallbladder stones, biliary complications have been reported to occur as frequently as approximately 20% while waiting for cholecystectomy 7 . Therefore, early cholecystectomy is preferable, but laparoscopic cholecystectomy often requires a waiting period of several weeks for treatment due to patient preference, lack of surgeons, COVID‐19 pandemic, and other factors 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, we observed an increased number of AC patients who presented with gangrenous acute cholecystitis. An early case series showed that COVID-19 infection and pneumonia were associated with GC with increased morbidity and mortality, mainly in elderly and frail patients [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%